The multiple biological activities of hyperoside: from molecular mechanisms to therapeutic perspectives in neoplastic and non-neoplastic diseases - Zhang, Weisong; Wang, Rui; Guo, Rongqi; Yi, Zhongquan; Wang, Yihao; Wang, Hao; Li, Yangyang; Li, Xia; Song, Jianxiang (Frontiers in Pharmacology, 2025)
In recent years, hyperoside (quercetin 3-O-β-D-galactopyranoside) has garnered significant attention due to its diverse biological effects, which include vasoprotective, antioxidant, anti-inflammatory, and anti-tumor properties. Notably, hyperoside has shown remarkable potential in cancer therapy by targeting multiple mechanisms; it induces apoptosis, inhibits proliferation, blocks angiogenesis, and reduces the metastatic potential of cancer cells. Furthermore, hyperoside enhances the sensitivity of cancer cells to chemotherapy by modulating key signaling pathways. Beyond neoplastic diseases, hyperoside also presents promising therapeutic applications in managing non-cancerous conditions such as diabetes, Alzheimer’s disease, and pulmonary fibrosis. This review comprehensively examines the molecular mechanisms underlying hyperoside’s anti-cancer effects and highlights its role in the treatment of cancers, including lung and colorectal cancers. Additionally, it explores the latest research on hyperoside’s potential in addressing non-neoplastic conditions, such as pulmonary fibrosis, diabetes, and Parkinson’s disease. By summarizing current findings, this review underscores the unique therapeutic value of hyperoside and its potential as a multifunctional treatment in both neoplastic and non-neoplastic contexts.